PELAKSANAAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU TAHUN 2017 - Tona Doli Silitonga (STIKes Hang Tuah Pekanbaru, 2019)
ABSTRACT Hospital Management Information System (SIMRS) is a communication information technology that processes and integrates the entire process flow of hospital services in the form of network coordination, reporting and administrative procedures to obtain information accurately and accurately, and is part of health information system. Handsome Mental Hospital of Riau Province has implemented SIMRS starting from 2013 and has been integrated, but not all are integrated from the existing structure at the Handsome Soul Hospital of Riau Province. The results obtained Man (Human), Money (Cost), Material (Materials), Machine (Machine), Motode (Method). It is of concern in the implementation of SIMRS, because the implementation of SIMRS has not been implemented as a whole and there are still obstacles in some parts related to the implementation of SIMRS. Keywords: Hospital Management Information System (SIMRS)